Ecology of bacterial endophytes associated with wetland plants growing in textile effluent for pollutant-degradation and plant growth-promotion potentials. (1st November 2016) - Shehzadi, M.; Fatima, K.; Imran, A.; Mirza, M. S.; Khan, Q. M.; Afzal, M.
Abstract : In this study, 41 culturable endophytic bacteria were isolated from the roots and shoots of three wetland plants, Typha domingensis, Pistia stratiotes and Eichhornia crassipes, and identified by 16S rRNA gene sequencing. Textile effluent-degrading and plant growth-promoting activities of these endophytes were determined. The analysis of endophytic bacterial communities indicated that plant species had a pronounced effect on endophytic bacterial association and maximum endophytes (56.5%) were associated with T. domingensis . These endophytic bacteria mainly belonged to different species of the genera Bacillus (39%), Microbacterium (12%) and Halomonas (12%). Eight of the 41 strains showing maximum efficiency of textile effluent degradation also exhibited plant growth-promoting activities such as production of indole-3-acetic acid and siderophore, presence of 1-amino-cyclopropane-1-carboxylic acid deaminase, and solubilization of inorganic phosphorous. This is the first study describing the diversity and plant-beneficial characteristics of the textile effluent-degrading endophytic bacteria associated with wetland plants. T. domingensis showed better growth in textile effluent and also hosted maximum number of endophytic bacteria in roots and shoots. The interactions between T. domingensis and its associated endophytic bacteria could be exploited to enhance the efficiency of constructed wetlands during the remediation of industrial effluent.